1996
DOI: 10.1111/j.1365-2036.1996.tb00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of water immersion stress‐induced gastric lesions through the enhancement of nitric oxide synthase activity in rats

Abstract: Background: Gastric mucosal microcirculation is an important factor in the protection of gastric mucosa, and nitric oxide (NO) plays a crucial role in the regulation of regional blood flow. This study was designed to evaluate the effect of cetraxate, an antiulcer drug, on water immersion stress-induced gastric lesions in relation to the changes in NO synthase activity. Methods: Gastric lesions were induced in rats by water immersion stress. The effects of cetraxate on NO synthase activity with or without stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2000
2000
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 21 publications
1
19
1
Order By: Relevance
“…Cetraxate, an anti‐ulcer drug with mucosal protective effects, is reported to increase MBF by enhancing nitric oxide synthase activity 17 . Tachi et al demonstrated that cetraxate increased NO synthase activity in rats with and without stress treatment, and prevented stress‐induced decreases of several PGs in gastric mucosa 18 . In addition, a recently published study has demonstrated that the addition of cetraxate to proton pump inhibitor (PPI)‐based triple H. pylori eradication treatment augmented the eradication rate, especially in smokers, probably by increasing gastric MBF 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cetraxate, an anti‐ulcer drug with mucosal protective effects, is reported to increase MBF by enhancing nitric oxide synthase activity 17 . Tachi et al demonstrated that cetraxate increased NO synthase activity in rats with and without stress treatment, and prevented stress‐induced decreases of several PGs in gastric mucosa 18 . In addition, a recently published study has demonstrated that the addition of cetraxate to proton pump inhibitor (PPI)‐based triple H. pylori eradication treatment augmented the eradication rate, especially in smokers, probably by increasing gastric MBF 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Cetraxate is a widely used anti‐ulcer drug with protective effects on the mucosa. The anti‐ulcer activity of this drug is ascribed to the increase in MBF caused by enhancing nitric oxide synthase activity 17,18 . This study was designed to investigate the effect of H. pylori infection on MBF during human gastric ulcer healing, and the effect of cetraxate on H. pylori ‐induced changes in MBF.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that such an effect is not a result of any direct vasodilatory action but is the consequence of preventing an action of this NSAID, which, in turn, leads to a reduction of gastric perfusion. Although the mechanisms responsible for these effects may vary Reduction in gastric blood flow after NOS inhibition is associated with: 1Stress induced gastric damage (Qiu et al, 1996) 1Ethanol induced gastric damage (Masuda et al, 1995;Qiu et al, 1996) 2Gastric mucosa epithelial growth (Dembinski et al, 1995) 2Ulcer healing (Takeuchi et al, 1997) NO mediates gastroprotection and mucosal hyperemia induced by: Antiulcer drugs Aluminum antacids (Konturek et al, 1992) Cetraxate (Tachi et al, 1996) Lansoprazol (Murakami et al, 1996) Sucralfate ) Hormones Cholecystokinin Leptin (Brzozowski et al, 1999b) Pentagastrin …”
Section: Mucosal Blood Flowmentioning
confidence: 98%
“…Its activity is ascribed to promotion of an increase in gastric mucosal blood flow (29). Tachi et al showed that cetraxate might enhance nitric oxide synthase activity and prevent a decrease in the mucosal prostaglandin content, resulting in an increase in gastric mucosal blood flow (30). The addition of cetraxate also has been reported to improve the eradication rate of H. pylori (31).…”
Section: Discussionmentioning
confidence: 97%